The Common Microcredentials Framework for MOOCs and Short Learning Programmes - Alessandra Antonaci; Piet Henderikx; George Ubachs (Journal of Innovation in Polytechnic Education)
In today’s society, both employees and job seekers have to keep their knowledge and skills up to date, without investing too much time in doing so. The traditional offer of European higher education institutions does not meet this need, as continuing education programs are not flexibly organised, and most people cannot invest years in a bachelor’s or master’s degree. As a consequence, to meet these learners’ needs, universities are required to provide more compact qualifications. Online micro-credentials and short learning programmes are formats that respond to this need. After defining both the terms microcredentials and short learning programmes, this paper introduces a framework developed within the European MOOCs Consortium: the Common Microcredentials Framework- CMF, whose final aim is, from one side of facilitating the development of these types of programmes among traditional institutions and MOOC providers, and, from the other side, their recognition among European higher education institutions.